Peningkatan Pengetahuan Masyarakat melalui Edukasi Penggunaan Dexamethasone Secara Rasional di Klinik Armina Sakti Kota Bengkulu - Lusiana Lusiana; Septi Wulandari; Annadine Zahrina Ajeqy; Rahmadannisa Dwi Amanda; Ridwan Hartadi; Elsa Nur Rahmadina; Elsi Febriyani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Inappropriate use of dexamethasone without adequate knowledge or health-professional supervision poses significant risks to the community, particularly through its informal circulation as a